#### Answer

$ 2x ( x+7) (x-6)$

#### Work Step by Step

$2x^3 + 2x^2 -84x = 2x( x^2 + x - 42) = 2x ( x^2 +7x - 6x - 42) = 2x (x (x+7) - 6 (x +7)) = 2x ( x+7) (x-6)$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$ 2x ( x+7) (x-6)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.